2013
DOI: 10.1111/jdv.12223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of intravenous immunoglobulins for the treatment of dermatomyositis skin lesions without muscle disease

Abstract: IVIg may be an effective and safe treatment for DM with isolated skin involvement. Relapse occurred frequently, but treatment with a new course of IVIg was successful. Controlled studies are required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Thirty‐one patients used IVIG, including two patients with acute ILD . In most cases 2 g kg −1 was given over two consecutive days and repeated at monthly intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐one patients used IVIG, including two patients with acute ILD . In most cases 2 g kg −1 was given over two consecutive days and repeated at monthly intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Side‐effects were headache (12 patients), nausea (five patients), fever (two patients) and hypertension (one patient). Two patients discontinued IVIG due to headaches on the first cycle …”
Section: Resultsmentioning
confidence: 99%
“…Femia and colleagues retrospectively reviewed 13 patients with DM who showed clinical improvement with IVIG for refractory skin disease, and found that 8 of the patients achieved complete response . Similarly, Bounfour and colleagues retrospectively reviewed 27 patients with refractory cutaneous DM, finding that 23 patients showed skin improvement with IVIG treatment …”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, Bounfour and colleagues retrospectively reviewed 27 patients with refractory cutaneous DM, finding that 23 patients showed skin improvement with IVIG treatment. 8 In the current study, we assessed 42 patients with DM treated with IVIG for refractory DM skin disease with/ without refractory myositis and/or ILD, who had clinical data at time of DM diagnosis and IVIG initiation available for review. The majority (83%) showed cutaneous improvement with IVIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation